A Highly Efficient Copper(II)-Catalyzed Cross-Dehydrogenative-Coupling Reaction of N-Arylglycine Esters with 2-Arylimidazo[1,2-a]pyridines - Zhu, Zhi-Qiang; Xiao, Li-Jin; Chen, Ying; Xie, Zong-Bo; Zhu, Hai-Bo; Le, Zhang-Gao (Synthesis, 2018)
A rapid and highly efficient copper(II)-catalyzed cross-dehydrogenative coupling (CDC) reaction of N-arylglycine esters with imidazo[1,2-a]pyridines has been described. A broad range of N-arylglycine esters underwent the CDC reaction smoothly with 2-arylimidazo[1,2-a]pyridines to give α-substituted α-amino acid esters in excellent yields. This synthetic method has the advantages of high yields, good functional groups compatibility, simple operation, and mild reaction conditions. A possible mechanism for the CDC reaction is also proposed. The use of a copper salt as the catalyst and air as the terminal oxidant makes this transformation sustainable and practical.
Keywords: cross-dehydrogenative coupling; copper; glycine ester; imidazo[1,2-a]pyridine; imine